ISOLATION AND PARTIAL PURIFICATION OF CYCLOOXYGENASE-2 FROM BLADDER CANCER PATIENTS AND ESTIMATION OF ITS MOLECULAR WEIGHT - Mohammed Hussin Mousa1, Mohammed Bahry Hasan2, (Chelonian Research Foundation, 2024)
The study was carried out in the city of Mosul during the period 3/1/2022 until 6/1/2023 and included 75 people with bladder cancer, 68 males and 7 females, whose ages ranged between 50-80 years. The study included the isolation and purification of the cyclooxygenase-2 enzyme from blood serum. Patients with bladder cancer and studying its characteristics using techniques of salt displacement, membrane sorting, and ion exchange chromatography, and estimating its approximate molecular weight by electromigration technique. The study was carried out in the laboratories of the College of Science/University of Mosul. The results showed the presence of one distinct peak for the protein solution, and the purification process was relatively effective, with recovery of more than 50.82% of the enzyme activity. The approximate molecular weight was estimated using the electrophoretic migration technique, as a distinctive protein band was found that was used in estimating the approximate molecular weight of the enzyme, which is equal to (72). ) kilodaltons, and the optimal conditions for measuring enzyme activity were 5 minutes for reaction time, 7.5 for pH, temperature of 40°C, and 0.6 mM concentration of the substrate. Keywords: bladder cancer, cyclooxygenase-2, salt displacement precipitation, membrane sorting, ion exchange chromatography, electromigration technique